2016
DOI: 10.1080/1028415x.2016.1221496
|View full text |Cite
|
Sign up to set email alerts
|

Spirulinadiet to lactating mothers protects the antioxidant system and reduces inflammation in post-natal brain after systemic inflammation

Abstract: A Spirulina diet given to lactating mothers can protect against neuroinflammation and decreased antioxidant defence in brain of suckling pups subjected to peripheral inflammation, possibly via decreased activation of p38 and high levels of the antioxidant miRNA-146a.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
8
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 46 publications
(51 reference statements)
1
8
0
Order By: Relevance
“…The effect on IL-1β is in agreement with earlier studies using this model [6] and appears to be region specific as the effect of LPS was normalized in cortex after 65 days [19]. The decrease in Nrf2 has to our knowledge not been demonstrated earlier and could be an important mechanism behind the elevated vulnerability in the substantia nigra after neonatal infection [6].…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…The effect on IL-1β is in agreement with earlier studies using this model [6] and appears to be region specific as the effect of LPS was normalized in cortex after 65 days [19]. The decrease in Nrf2 has to our knowledge not been demonstrated earlier and could be an important mechanism behind the elevated vulnerability in the substantia nigra after neonatal infection [6].…”
Section: Discussionsupporting
confidence: 89%
“…From these results we argue that one mechanism by which increased neuroinflammtion can mediate increased vulnerability is via a decreased Nrf2 function. This prolonged effect on Nrf2 is evident in the substantia nigra but not in cortex [19], which, at least partly, could explain the increased vulnerability to toxins of substantia nigra in animals subjected to neonatal inflammation [9] and could potentially be an important determinant behind sporadic Parkinson’s disease (PD).…”
Section: Discussionmentioning
confidence: 99%
“…Nrf2 is a major transcription factor that regulates cell antioxidant response. Nrf2 is transported to the nucleus under oxidative stress and binds to the antioxidant response elements (ARE) to regulate the expression of antioxidant enzymes such as HO-1 [37].In the previous study, the expression of the Nrf2-systerm (Nrf2 and HO-1) in rat brain were still increased 3 days after the LPS systemic injection, decreased by 7 days and then gradually normalized after LPS [38]. Our results showed that the contents of Nrf2 and HO-1 were nearly normalized in the hippocampus of rats after 14 days of LPS-induced.…”
Section: Discussionmentioning
confidence: 94%
“…Nrf2 is transported to the nucleus under oxidative stress and binds to the antioxidant response elements (ARE) to regulate the expression of antioxidant enzymes such as HO-1 [37].In the previous study, the expression of the Nrf2-systerm (Nrf2 and HO-1) in rat brain were still increased 3 days after the LPS systemic injection, decreased by 7 days and then gradually normalized after LPS [38]. Our results showed that the contents of Nrf2 and HO-1 were nearly normalized in the hippocampus of rats after 14 days of LPS-induced.…”
Section: Discussionmentioning
confidence: 94%